Synthesis and Characterization of Double Crystalline Cyclic Diblock Copolymers of Poly(ε‐caprolactone) and Poly(l(d)‐lactide) (c(PCL‐b‐ PL(D)LA)). Issue 20 (29th August 2016) - Liénard, Romain; Zaldua, Nerea; Josse, Thomas; Winter, Julien De; Zubitur, Manuela; Mugica, Agurtzane; Iturrospe, Amaia; Arbe, Arantxa; Coulembier, Olivier; Müller, Alejandro J.
Abstract : The synthesis of symmetric cyclo poly(ε‐caprolactone)– block –poly(l (d )‐lactide) ( c (PCL– b –PL(D)LA)) by combining ring‐opening polymerization of ε‐caprolactone and lactides and subsequent click chemistry reaction of the linear precursors containing antagonist functionalities is presented. The two blocks can sequentially crystallize and self‐assemble into double crystalline spherulitic superstructures. The cyclic chain topology significantly affects both the nucleation and the crystallization of each constituent, as gathered from a comparison of the behavior of linear precursors and cyclic block copolymers. The stereochemistry of the PLA block does not have a significant effect on the nonisothermal crystallization of both linear and cyclo PCL‐ b ‐PDLA and PCL‐ b ‐PLLA copolymers. Abstract : The successful synthesis of symmetric cyclo poly(ε‐caprolactone)– block –poly(l(d)‐lactide) ( c (PCL– b –PL(D)LA)) by combining ring‐opening polymerization and subsequent click chemistry reactions has been achieved. The blocks can sequentially crystallize and self‐assemble into double crystalline spherulites. Chain topology affects overall crystallization of each block, as determined from a comparison of the behavior of linear precursors and cyclic block copolymers.